The Development of an Ebook Integrated with Learning Management System to Improve Student's Metacognition Ability - Sutrisnawati Mardin; Achmad Ramadhan; Masrianih Ismail (Journal of Educational Science and Technology (EST), 2022)
This study aims to develop an ebook that is integrated with a Learning Management System (LMS) to improve students' metacognition skills. The research uses the ADDIE development model (Assumption, Design, Development, Implementation, Evaluation). The research data were obtained from 40 students who filled out the questionnaire and took the pretest and posttest. The effectiveness of the ebook on improving metacognitive skills used N-Gain analysis and to determine the difference between the experimental and control classes, a T-test was performed, using One Group Pretest and Post-test Design. The results showed that ebook development was very good. The development of ebooks integrated with LMS can significantly improve students' metacognitive abilities. Thus, this study recommends that lecturers use ebooks that are integrated into the learning management system so that learning can run effectively to improve students' metacognitive abilities.Â Â